Cleantech : Prospects and Challenges - Shakeel, Shah Rukh (Associação Journal of Innovation Management, 2021)
The issue of climate change, greenhouse gas emissions, global warming, and their effect on nature and the ecosystem has raised serious concerns. The desire to sustain economic growth and development while keeping a check on the environmental footprints is one of the leading challenges the contemporary world is currently facing. To ensure sustained growth, there is a need for technologies and solutions that has the potential to meet industrial needs without compromising the environment. Cleantech offers a possibility to address these needs in a sustainable and environmentally friendly manner. Cleantech, being an umbrella term, is often confused and misunderstood, in terms of its definition and scope. This study seeks to explore what cleantech actually is, how this sector came into prominence, what are the driving factors behind its surge, and what kind of socio-economic, technical, and regulatory prerequisites are necessary for the advancement of this sector.
Keywords: Socio-economic; Technical; Regulatory; Emergence; Diffusion; Ecosystem; Drivers; Barriers; cleantech; fi=Markkinointi|en=Marketing|